Mapping of a mutation affecting regulation of iron uptake systems in Escherichia coli K-12. - Bagg, A (1985)
The site of a mutation resulting in constitutive derepression of iron uptake systems has been localized at 15.7 min on the genetic map of Escherichia coli K-12.